Two Pathways of Subsurface Spiciness Anomalies in the Subtropical South Pacific - Sasaki, Yoshi N.; Iwai, Yuma (Frontiers in Climate, 2022)
Subduction and migration of density-compensated (warm/salty or cool/fresh) temperature and salinity water-mass anomalies on isopycnals, referred to as spiciness anomalies, are examined in the subtropical gyre of the South Pacific using an observational dataset. The present results demonstrate that the spiciness anomalies are found to follow two pathways from the subtropical region to the tropical area on the 25–25.5σθ isopycnals. The water masses of one pathway subduct south of 20°S and mainly flow westward via the mean geostrophic current to the western boundary region. The water masses of this pathway correspond to the salinity maximum on these isopycnals as well as the bottom of the South Pacific Tropical Water. Positive temperature and salinity trends were prominent along this pathway during the study period. In the other pathway, the water masses subduct north of 20°S and go directly to the tropics through the interior region. Decadal variability of the spiciness anomalies is prominent along this pathway. In both pathways, sea surface salinity variability likely plays an important role in generating the spiciness anomalies on the isopycnals. A passive tracer experiment revealed that the advection by the South Equatorial Countercurrent (SECC) divides these two pathways. Hence, SECC plays a key role in determining whether a spiciness anomaly propagates through the interior region or the western boundary region.